A randomized, prospective, open label comparative study of the efficacy of azilsartan and ramipril in the management of hypertension in patients with type-2 diabetes mellitus - Siddiqua, Husna; Subhani, Ghulam (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Patients with diabetes are prone to have hypertension. Hypertension is risk factors for complications of the vascular system, cardiovascular diseases and leads to atherosclerosis. It has been estimated that the diabetics tend to have about two times more risk of having hypertension than the general population. Objective of current study is to study and compare the efficacy of azilsartan and ramipril in the management of Hypertensive patients with type 2 diabetes mellitus Methods: randomized, prospective, open label comparative study was carried out among 60 known cases of diabetes mellitus type-2 with hypertension. Patients were randomly allocated into two groups: group-A (N=30) taking ACE Inhibitor tablet ramipril 5 mg Once daily orally. Group-B (N=30) taking angiotensin II receptor antagonist tablet azilsartan 40 mg once daily orally. At the commencement of the trial, patients were subjected to thorough clinical examination with necessary investigations and base line values were recorded. Results: Both the groups were comparable for age, sex and treatment taken. There was a significant reduction in the mean arterial pressure (17.43 for azilsartan group vs. 14.5 for ramipril group) (mmHg), creatinine clearance (mean reduction of 18.8 for azilsartan group vs. 13.94 for ramipril group), and urinary albumin excretion (mean reduction of 29.74 in azilsartan group vs. 17.25 for ramipril group). In azilsartan group the reduction was more in all parameters compared to ramipril group without effecting renal parameters. Conclusions: Azilsartan was more effective in reducing the mean arterial pressure (mmHg), creatinine clearance as well as urinary albumin excretion in Hypertensive patients with Type 2 diabetes mellitus without effecting renal parameters.